Global ecological success of Thalassoma fishes in extreme coral reef habitats - Christopher J. Fulton; Peter C. Wainwright; Andrew S. Hoey; David R. Bellwood (Ecology and Evolution, 2017)
Abstract Phenotypic adaptations can allow organisms to relax abiotic selection and facilitate their ecological success in challenging habitats, yet we have relatively little data for the prevalence of this phenomenon at macroecological scales. Using data on the relative abundance of coral reef wrasses and parrotfishes (f. Labridae) spread across three ocean basins and the Red Sea, we reveal the consistent global dominance of extreme wave‐swept habitats by fishes in the genus Thalassoma, with abundances up to 15 times higher than any other labrid. A key locomotor modification—a winged pectoral fin that facilitates efficient underwater flight in high‐flow environments—is likely to have underpinned this global success, as numerical dominance by Thalassoma was contingent upon the presence of high‐intensity wave energy. The ecological success of the most abundant species also varied with species richness and the presence of congeneric competitors. While several fish taxa have independently evolved winged pectoral fins, Thalassoma appears to have combined efficient high‐speed swimming (to relax abiotic selection) with trophic versatility (to maximize exploitation of rich resources) to exploit and dominate extreme coral reef habitats around the world.